2007
DOI: 10.1016/j.rmed.2006.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase markers for the differentiation of infectious and malignant pleural effusions

Abstract: Acute-phase markers, such as C-reactive protein (CRP), interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-alpha), have been studied in inflammatory and malignant disorders. We examined the diagnostic value of these markers for the differentiation among parapneumonic, tuberculous and malignant effusions. We studied 124 patients with pleural effusions, classified as exudates [total (n=97), parapneumonic (n=15), tuberculous (n=25), malignant (n=57)] and transudates due to congestive heart failure (n=27). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
42
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 26 publications
8
42
0
1
Order By: Relevance
“…CRP CRP, an acute-phase reactant released from the liver, is a common diagnostic test within hospital laboratories for the screening or monitoring of infections and noninfectious inflammatory diseases. CRP levels have been studied in pleural fluid and have been found to be higher in PPEs than in other types of exudative or transudative effusions [5][6][7]. We showed that a pleural fluid CRP level .80 mg?L -1 argues for the presence of a PPE (LR+ 7.4), whereas CRP levels ,20 mg?L -1 are a strong indicator against an infectious pleural effusion, whether of bacterial or mycobacterial nature (LR-0.22).…”
Section: Discriminating Ppe From Other Aetiologiesmentioning
confidence: 99%
“…CRP CRP, an acute-phase reactant released from the liver, is a common diagnostic test within hospital laboratories for the screening or monitoring of infections and noninfectious inflammatory diseases. CRP levels have been studied in pleural fluid and have been found to be higher in PPEs than in other types of exudative or transudative effusions [5][6][7]. We showed that a pleural fluid CRP level .80 mg?L -1 argues for the presence of a PPE (LR+ 7.4), whereas CRP levels ,20 mg?L -1 are a strong indicator against an infectious pleural effusion, whether of bacterial or mycobacterial nature (LR-0.22).…”
Section: Discriminating Ppe From Other Aetiologiesmentioning
confidence: 99%
“…Higher SF CRP levels reXect greater degrees of joints inXammation in RA and OA [16]. CRP level is also used for the diVerentiation of infectious, tuberculosis and malignant pleural eVusions [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of interleukin (IL)-6 and IL-8 but decreased levels of the soluble form of the interleukin 6 receptor (sIL-6R) were found in pleural effusion fluid of patients with lung cancer and malignant pleural effusions (CA) and could be used for differential diagnosis against effusions of tuberculous origins (TB) [1,2]. In another study matrix metalloproteinases (MMP) and tissue inhibitors of metalloproteinases (TIMP) were examined.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-γ, IL-12p40, and IL-6 proved useful in differentiating tuberculous and malignant effusions [12]. C-reactive protein (CRP), IL-6, and TNF-α provided useful information for the differentiation of parapneumonic, tuberculous and malignant effusions in clinical practice [2]. Applying a decision tree analysis that contained age, temperature, pleural fluid ADA, and LDH was helpful in the differential diagnosis of tuberculous and malignant pleural effusions [13].…”
Section: Introductionmentioning
confidence: 99%